Risk Factors for Nipah Virus Infection among Abattoir Workers in Singapore - Chew, Madeleine H. L.; Arguin, Paul M.; Shay, David K.; Goh, Kee-Tai; Rollin, Pierre E.; Shieh, Wun-Ju; Zaki, Sherif R.; Rota, Paul A.; Ling, Ai-Ee; Ksiazek, Thomas G.; Chew, Suok-Kai; Anderson, Larry J. (The Journal of infectious diseases, 2000)
During 10–19 March 1999, 11 workers in 1 of 2 Singaporean abattoirs developed Nipahvirus associated encephalitis or pneumonia, resulting in 1 fatality. A case-control study was conducted to determine occupational risk factors for infection. Case patients were abattoir A workers who had anti-Nipah IgM antibodies; control subjects were randomly selected abattoir A workers who tested negative for anti-Nipah IgM. All 13 case patients versus 26 (63%) of 41 control subjects reported contact with live pigs (P = .01). Swine importation from Malaysian states concurrently experiencing a Nipah virus outbreak was banned on 3 March 1999; on 19 March 1999, importation of Malaysian pigs was banned, and abattoirs were closed. No unusual illnesses among pigs processed during February–March were reported. Contact with live pigs appeared to be the most important risk factor for human Nipah virus infection. Direct contact with live, potentially infected pigs should be minimized to prevent transmission of this potentially fatal zoonosis to humans.